Survey of ICT and Education in Africa : Namibia Country Report - Isaacs, Shafika (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Namibia has played a pioneering and visionary role in Africa in the area of ICTs in education and serves as a beacon for many organizations and groups operating across the continent. Namibia offers innovative options on affordable and sustainable access to ICTs through the active involvement of local youth under the leadership of SchoolNet Namibia. In addition to a visionary national ICT for education policy, the Namibian government has also taken the lead in committing a dedicated budget to support ICTs in education and the establishment of machinery for coordinated multi-stakeholder collaboration.